Physical examination &​ health assessment - Jarvis, Carolyn (Elsevier, 2016)
With an easy-to-read approach and unmatched learning resources, this text offers a clear, logical, and holistic approach to physical exams across the lifespan. A total of 1,200 illustrations, checklists of key exam steps, and practical insights ensure that you learn all the physical exam skills you need to know. Written by Carolyn Jarvis, an experienced educator and clinician, this gold standard in physical examination reflects what is going on in nursing today with coverage of emerging trends and the latest on evidence-based practice